Suntik Mati dalam Tinjauan Hukum Syariah - Aliya Azizah; Puteri Nabila Rahman (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
Euthanasia, also known as “Assisted Suicide”, is the deliberate act of ending a person's life to relieve their suffering that cannot be relieved by treatment. This has sparked debate in various fields, including in the field of Islamic law or syariah. In the perspective of syariah law, life is considered a gift from Allah that must be fully protected. Protection of life is the main goal of Syariah (maqasid al-shariah). Therefore, Islam strictly prohibits any attempt to end life intentionally, including euthanasia. According to syariah law, only Allah has full rights over a person's life and death. Euthanasia is considered a violation of the basic principles of syariah which prohibit killing, whether of oneself or another person. Although reasons such as suffering and pain are often used to justify euthanasia, in the view of syariah, suffering is considered a test that must be faced with patience and devotion to Allah. This article aims to examine in depth the view of syariah law towards lethal injection.